Application of the Incremental Modal Pushover Analysis to Bridges Subjected to Near-Fault Ground Motions - Alessandro Vittorio Bergami; Gabriele Fiorentino; Davide Lavorato; Bruno Briseghella; Camillo Nuti (Applied Sciences, 2020)
Near-fault events can cause severe damage to civil structures, including bridges. Many studies have demonstrated that the seismic assessment is not straightforward. Usually, dealing with near-fault ground motion, the structural analysis is performed using Nonlinear Response-History Analysis (NRHA) but in the last years, many authors have tested existing pushover-based procedures originally developed and validated using far-field events. Between those procedures, the Incremental Modal Pushover Analysis (IMPAβ) is a pushover-based procedure specifically developed for bridges that, in this work, was applied to a case study considering near-fault pulse-like ground motion records. The records were analyzed and selected from the European Strong Motion Database. In the paper the results obtained with IMPAβ together with other standard pushover procedures, are compared with NRHA and incremental dynamic analyses; the vertical component of the motion has been also considered. Results obtained with the bridge case study demonstrate that the vertical seismic action has a minor influence on the structural response and that IMPAβ is confirmed as a very effective pushover-based method that can be applied also for near-fault events.